Do Wealth Shocks Affect Health? New Evidence from the Housing Boom - Fichera, Eleonora (Health Econ, 2016)
We exploit large exogenous changes in housing wealth to examine the impact of wealth gains and losses on individual health. In UK household, panel data house price increases, which endow owners with greater wealth, lower the likelihood of home owners exhibiting a range of non‐chronic health conditions and improve their self‐assessed health with no effect on their psychological health. These effects are not transitory and persist over a 10‐year period. Using a range of fixed effects models, we provide robust evidence that these results are not biased by reverse causality or omitted factors. For owners' wealth gains affect labour supply and leisure choices indicating that house price increases allow individuals to reduce intensity of work with commensurate health benefits. © 2016 The Authors. Health Economics Published by John Wiley & Sons, Ltd.